Cooperative control of multi-robot system - Xu, Cong. (2009)
The technology development that came along in the last century with the advent of wireless communication brought a breadth of innovation and provided ways to efficiently share information between systems. This project studies several finite time consensus control algorithms for multi-robot system and presents simulation in Matlab environment. First, Wei’Ren’s distributed consensus control [3] and S. Mastellone’s non-centralized algorithm [4] are reviewed. Also, S. Mastellone’s algorithm is studied in detail and the assumptions are discussed. Then the Matlab simulation of S. Mastellone’s algorithm is carried out and shows well consensus control. Last, LabVIEW programs are written to send and retrieve data in multi-robot system for the SIMTech project.